2002
DOI: 10.2298/hel0236137p
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of resistance to a highly virulent race F of Orobanche cumana Wallr. in a sunflower line derived from interspecific amphiploids

Abstract: Broomrape (Orobanche cumana Wallr.) populations belonging to the new race F in Spain have overcome all known resistance genes, Or 1 to Or 5 , in cultivated sunflower (Helianthus annuus L.) and are spreading rapidly. Resistance to race F of this parasitic weed has been found in wild perennial species of Helianthus and has been introgressed into cultivated sunflower. The objective of this study was to characterize the inheritance of resistance genes in cultivated sunflower derived from wild perennial species H. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
30
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 7 publications
4
30
0
1
Order By: Relevance
“…However, the terminology used for race identification is to some extent confusing because the same race classification is used in Genetic studies on resistance to broomrape in sunflower have confirmed in most cases control of the trait by single dominant genes, as expected for a gene for gene interaction. This has been reported for races E (Vranceanu et al, 1980;Ish-Shalom-Gordon et al, 1993;Lu et al, 2000;Pérez-Vich et al, 2004;Sukno et al, 1999), F (Pacureanu-Joita et al, 2004;Pérez-Vich et al, 2002), and G (Velasco et al, 2012). Full demonstration of the occurrence of a gene-forgene interaction in the O. cumana-sunflower was provided by Rodríguez-Ojeda, Pineda-Martos et al (2013), who showed that O. cumana race E avirulence in presence of the resistance gene Or5 was inherited as a single dominant gene.…”
Section: Genetics Of Resistance and Avirulence: The Gene-for-gene Intsupporting
confidence: 59%
“…However, the terminology used for race identification is to some extent confusing because the same race classification is used in Genetic studies on resistance to broomrape in sunflower have confirmed in most cases control of the trait by single dominant genes, as expected for a gene for gene interaction. This has been reported for races E (Vranceanu et al, 1980;Ish-Shalom-Gordon et al, 1993;Lu et al, 2000;Pérez-Vich et al, 2004;Sukno et al, 1999), F (Pacureanu-Joita et al, 2004;Pérez-Vich et al, 2002), and G (Velasco et al, 2012). Full demonstration of the occurrence of a gene-forgene interaction in the O. cumana-sunflower was provided by Rodríguez-Ojeda, Pineda-Martos et al (2013), who showed that O. cumana race E avirulence in presence of the resistance gene Or5 was inherited as a single dominant gene.…”
Section: Genetics Of Resistance and Avirulence: The Gene-for-gene Intsupporting
confidence: 59%
“…In contrast to races A though E, initial genetic studies on resistance to race F concluded the presence of recessive alleles at two independent loci named Or 6 and Or 7 (Rodríguez-Ojeda et al, 2001;Akhtouch et al, 2002). Contrarily, Pérez-Vich et al (2002) found that resistance to race F in sunflower line J1 derived from wild species was controlled by dominant alleles at a single gene designated Or 6 . Further research revealed that dominance depended upon the susceptible parental line used for the cross, as in some cases F 1 hybrids segregated for resistance or were susceptible, which was attributed to the presence of a minor or modifying gene in some of the susceptible lines (Velasco et al, 2006).…”
Section: Characterization Of Resistancementioning
confidence: 99%
“…They have been used as an important "bridge" for transferring disease-resistance genes, abiotic stress-resistance/-tolerance genes, and other genes from wild relatives of wheat (Dvorák et al 1988;Jiang et al 1994;Colmer et al 1995;Martín et al 1999; Soliman et al 2001), rye (Wojciechowska andPudelska 2005;Islam et al 2007;Kang et al 2011;Malik et al 2011), and triticale (Kwiatek et al 2012). Amphiploids are also useful for studying the evolution and genetic diversity within a genus, such as Arabidopsis (Nasrallah et al Several interspecific sunflower amphiploids have been produced via embryo rescue and colchicine treatment with successful gene transfer reported (Jan and Chandler 1989;Jan and Fernandez-Martinez 2002;Pérez-Vich et al 2002;Feng and Jan 2008). Broomrape-resistance genes for race F in Spain were transferred from several wild Helianthus species into cultivated sunflower using interspecific amphiploids Pérez-Vich et al 2002).…”
mentioning
confidence: 99%
“…Amphiploids are also useful for studying the evolution and genetic diversity within a genus, such as Arabidopsis (Nasrallah et al Several interspecific sunflower amphiploids have been produced via embryo rescue and colchicine treatment with successful gene transfer reported (Jan and Chandler 1989;Jan and Fernandez-Martinez 2002;Pérez-Vich et al 2002;Feng and Jan 2008). Broomrape-resistance genes for race F in Spain were transferred from several wild Helianthus species into cultivated sunflower using interspecific amphiploids Pérez-Vich et al 2002). Amphiploids have shown resistance to Sclerotinia, a major fungal disease of sunflower (Jan et al 2006;Feng et al 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation